2019
DOI: 10.1088/1361-6463/ab2183
|View full text |Cite
|
Sign up to set email alerts
|

Field electron emission induced glow discharge in a nanodiamond vacuum diode

Abstract: The present letter extends the prior findings on self-induced heating of solid state field emission devices. It was found that a vacuum diode (base pressure ∼ 10 −9 Torr), that makes use of graphiterich polycrystalline diamond as cathode material, can switch from diode regime to resistor regime, to glow discharge plasma regime without any external perturbation, i.e. all transitions are self-induced. Combined results of in situ field emission microscopy and ex situ electron microscopy and Raman spectroscopy sug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…1) Starting at low surface field, emission current is dominated by sp 2 -rich (N)UNCD sites which causes high β and low E turn−on in measurement. 2) When the surface field is increased in the conditioning progress, high localized emission current leads to thermally driven degradation and extinction of originally strong emitters [45] which may be presented as rf breakdowns. 3) At higher fields, sp 2 -poor (N)UNCD sites dominate the emission as sp 2 -rich locations on (N)UNCD surface are consumed as conditioning proceeds, leading to low β and high E turn−on .…”
Section: Discussionmentioning
confidence: 99%
“…1) Starting at low surface field, emission current is dominated by sp 2 -rich (N)UNCD sites which causes high β and low E turn−on in measurement. 2) When the surface field is increased in the conditioning progress, high localized emission current leads to thermally driven degradation and extinction of originally strong emitters [45] which may be presented as rf breakdowns. 3) At higher fields, sp 2 -poor (N)UNCD sites dominate the emission as sp 2 -rich locations on (N)UNCD surface are consumed as conditioning proceeds, leading to low β and high E turn−on .…”
Section: Discussionmentioning
confidence: 99%
“…Corona discharge can occur under variable air pressures [32][33][34][35], either below the standard atmospheric pressure [36], or even in vacuum conditions [37][38][39][40]. The precursor and trigger of vacuum discharges and breakdowns is the field emission [41]. Field emission is a kind of cold cathode emission where electrons directly tunnel from the cathode into the nearby gas molecules (also called Fowler-Nordheim tunneling of electrons) due to the very high electric fields at microscale dimensions.…”
Section: History Of Ionic Windmentioning
confidence: 99%
“…This value includes diamond that breaks down at ~10 GV/m [26]. Experimentally, this would likely result in an immediate failure of the cathode due to breakdown induced runaway of the cathode material [27,28]. Since the cathode was not observed to behave this way, it is concluded that high field data overestimates the field enhancement factor.…”
Section: Section V: Field Emission Cathode Performancementioning
confidence: 99%